Floating - Troy, Robin (MTV : Pocket Books, MTV, 1998)
A woman whose husband is in jail has an affair with his brother, but the two discover too many differences and part. The novel, a debut in fiction, is based on the winning manuscript in a contest of some five hundred entries.
Keywords: Fiction; Fiction; Arizona; Fiction; Married women; Fiction; Mothers and sons; Prisoners' spouses; dept.eng; faculty_collection